Molecular evidence of coinfection of Anaplasma species in small ruminants from Anhui Province, China. (August 2019) - Yang, Banghe; Sun, Entao; Wen, Yufeng; Ye, Changjiang; Liu, Fei; Jiang, Ping; Tao, Xianglin
Abstract: The species of the genus Anaplasma are obligate intracellular pathogens that threaten the health of both humans and animals. In this study, we investigated the presence of Anaplasma phagocytophilum, A. ovis and A. bovis in 203 healthy small ruminants (117 goats and 86 sheep) in Anhui Province, China. The overall coinfection of Anaplasma species occurred in 33.0% (67/203) of all studied samples. The infection rates of A. ovis, A. bovis, and A. phagocytophilum were 14.5%, 12.0%, and 4.3% in goats and 26.7%, 17.4% and 3.5% in sheep, respectively. Coinfection of A. ovis + A. bovis was predominant in this study, with overall rates of 21.4% in goats and 20.9% in sheep, while the overall coinfection rates of A. ovis + A. phagocytophilum and A. bovis + A. phagocytophilum were 7.7% and 2.6% in goats and 7.0% and 4.7% in sheep, respectively. The occurrence of three-pathogen coinfection was also found in the studied ruminants, with a rate of 0.9% in goats and 1.2% among sheep. Phylogenetic analysis based on msp4 sequences showed that there were differences in the A. ovis genotype between sheep and goats in this study.